2020
DOI: 10.1093/nar/gkaa1112
|View full text |Cite
|
Sign up to set email alerts
|

High-resolution visualization and quantification of nucleic acid–based therapeutics in cells and tissues using Nanoscale secondary ion mass spectrometry (NanoSIMS)

Abstract: Nucleic acid therapeutics (NATs) have proven useful in promoting the degradation of specific transcripts, modifying gene expression, and regulating mRNA splicing. In each situation, efficient delivery of nucleic acids to cells, tissues and intracellular compartments is crucial—both for optimizing efficacy and reducing side effects. Despite successes in NATs, our understanding of their cellular uptake and distribution in tissues is limited. Current methods have yielded insights into distribution of NATs within … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(42 citation statements)
references
References 56 publications
1
33
0
Order By: Relevance
“…To comprehensively identify metabolic pathways that are affected during bones diseases, we conducted an integrating enrichment and pathway topology analysis from the data of Table 1 by using Metabo Analyst 5.0 [ 94 ]. For this, we used the metabolites that are reported as significantly altered in osteoporosis, arthritis, and osteosarcoma.…”
Section: Metabolomics In Research Of Bone Diseasesmentioning
confidence: 99%
“…To comprehensively identify metabolic pathways that are affected during bones diseases, we conducted an integrating enrichment and pathway topology analysis from the data of Table 1 by using Metabo Analyst 5.0 [ 94 ]. For this, we used the metabolites that are reported as significantly altered in osteoporosis, arthritis, and osteosarcoma.…”
Section: Metabolomics In Research Of Bone Diseasesmentioning
confidence: 99%
“…This is because integrative analyses can be conducted, for example, DNA methylation, SVs, and haplotype information. It was reported that the accuracy of methylation calling from the long-read sequencing had high concordance with the short-read sequencing [78] . Therefore, DNA methylation analyses using long-read sequencing will flourish.…”
Section: Dna Methylation and Svsmentioning
confidence: 94%
“…Our group has also developed a method combining Nanopore-type sequencing and Enzymatic Methyl-seq (EM-seq) [77] , named nanoEM [78] . EM-seq converts bases from unmethylated cytosines to uracils using an enzymatic reaction that prevents the fragmentation of DNA libraries during bisulfite sequencing, which is used to determine the pattern of DNA methylation.…”
Section: Dna Methylation and Svsmentioning
confidence: 99%
“…Most of the enzyme structure-activity information available in the protein data bank ( accessed on 1 August 2021) or bioinformatics tools ( accessed on 1 August 2021) has been determined in aqueous media [ 50 , 51 ]. Enzyme structural stability in neat organic solvents or aqueous/organic biphasic media is commonly measured by activity assay.…”
Section: Ionic Liquids and Isolated Enzymesmentioning
confidence: 99%